2010
DOI: 10.1016/j.ijantimicag.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

High-level ciprofloxacin resistance among hospital-adapted Enterococcus faecium (CC17)

Abstract: Hospital-adapted Enterococcus faecium differ from their colonising variants in humans and animals by additional genomic content. Molecular typing based on multilocus sequence typing (MLST) allows allocation of isolates to specific clonal complexes (CCs), such as CC17 for hospital-adapted strains. Acquired ampicillin resistance is a specific feature of these hospital isolates, especially in Europe. A few recent reports have described acquired high-level ciprofloxacin resistance as a supposed feature of hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 47 publications
(75 reference statements)
3
42
0
3
Order By: Relevance
“…The numbers of infections and colonizations with vanB type VRE increased in a number of European countries during recent years ( Bourdon et al, 2011, Klare et al, 2010and Soderblom et al, 2010. The supposed growing incidence of vanB type enterococci may have different reasons and could only be partly explained by an increased incidence of vanB type resistant strains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The numbers of infections and colonizations with vanB type VRE increased in a number of European countries during recent years ( Bourdon et al, 2011, Klare et al, 2010and Soderblom et al, 2010. The supposed growing incidence of vanB type enterococci may have different reasons and could only be partly explained by an increased incidence of vanB type resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic and university laboratories send strains to us for (vancomycin/teicoplanin) resistance confirmation and molecular typing. Our enterococcal strain collection currently contains > 10,000 isolates, mainly from hospital surveillance and infections, but also from animals, food products, the environment, and stool colonisations in outpatients (Klare et al, 1995a, Klare et al, 1995b, Klare et al, 1999, Klare et al, 2005, Werner et al, 2007, Werner et al, 2010and Werner et al, 2011a. Until now, we collected and identified 1060 vanB strains including 982 vanB-positive E. faecium and 74 vanB-positive E. faecalis which were all from hospital patients.…”
Section: Strain Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…and the necessity of specific mutations in one or both A subunit genes to confer what is specified as high-level ciprofloxacin resistance (Onodera et al, 2002;Oyamada et al, 2006a;Oyamada et al, 2006b). Molecular studies with high-level ciprofloxacin-resistant clinical isolates revealed mutations in both A subunits associated with different levels of ciprofloxacin resistance, whereas mutations in gyrB and parE alleles were only infrequently found Leavis et al, 2006;Valdezate et al, 2009;Werner et al, 2010a).…”
Section: Fluoroquinolone Resistancementioning
confidence: 99%